2003
DOI: 10.1007/s00467-003-1152-y
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus-associated acute renal failure: diagnosis, treatment, and follow-up

Abstract: We retrospectively reviewed our experience of Epstein-Barr virus (EBV)-associated acute renal failure. Of 165 previously healthy children hospitalized with serologically proven primary EBV infection, 8 had acute renal failure, of whom 5 (group A) did not have virusassociated hemophagocytic syndrome (VAHS), while 3 (group B) did have VAHS. All had complications in four or more organ systems. Two patients in group A had renal biopsies showing acute tubulointerstitial nephritis, and the clinical and laboratory fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…64 More commonly, hepatitis A virus induces acute renal failure secondary to acute fulminant hepatitis. 65 Acute renal failure complicating other viral infections, such as Epstein-Barr virus 66 and dengue fever, 67…”
Section: Other Virusesmentioning
confidence: 99%
“…64 More commonly, hepatitis A virus induces acute renal failure secondary to acute fulminant hepatitis. 65 Acute renal failure complicating other viral infections, such as Epstein-Barr virus 66 and dengue fever, 67…”
Section: Other Virusesmentioning
confidence: 99%
“…The relationship between the re-emerging fatal renal failure and the EBV infection from several years ago evokes associations with previously reported cases. A researcher from a hospital in Taipei, China reported eight cases of acute renal failure in EBV-infected pediatric patients within 6 years, and two of these patients eventually died ( 7 ). This suggests that EBV infection-induced severe kidney damage is not uncommon and can seriously affect the prognosis if not treated aggressively.…”
Section: Discussionmentioning
confidence: 99%
“…In children, a few reports have described the various manifestations of EBV-associated nephropathy. A retrospective study of 165 children with primary EBV infection reported an AKI incidence of 5%, with TIN being the most common renal histology 4. NS in association with EBV infection was described in a 19-month-old girl who had resolution of proteinuria with abatement of EBV 3.…”
Section: Discussionmentioning
confidence: 99%